ANALYSIS OF PERCEIVED CONVENIENCE 4.0 AND DIGITAL EXPERIENCE QUALITY ON CONTINUANCE USAGE BEYOND BASIC FEATURE LIVIN' BY MANDIRI WITH AFFECTIVE TRUST AS MEDIATION IN MEDAN CITY - Hambali; Muhammad Dharma Tuah Putra; Dewi Nurmasari Pane (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze the influence of Perceived Convenience 4.0 and Digital Experience Quality on Continuance Usage Beyond Basic Features among users of the Livin' by Mandiri mobile banking application, with Affective Trust as a mediating variable. This study uses a quantitative approach with the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. Data were obtained from Livin' user respondents who have used basic features and have accessed features beyond basic. The results show that Perceived Convenience 4.0 and Digital Experience Quality have a significant positive effect on Affective Trust and continued use of advanced features. In addition, Affective Trust is proven to significantly mediate the relationship between convenience and digital experience on continuance usage, so emotional trust plays an important role in encouraging exploration of more complex features. These findings confirm that digital convenience and experience quality are key factors in building users' emotional relationships with the application, which ultimately increases the use of features beyond basic. This study provides theoretical contributions to the development of mobile banking user behavior models as well as practical implications for optimizing experience- and trust-based digital banking strategies.